(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The major part of the decade for education on sustainable development declared by United Nation in 2005 is over and it is the time to review the outcomes of the efforts of national and international educational and research communities. These results differ greatly. One of the ways to grasp the picture is to look at the map of regional centres of expertise on education for sustainable development organized under the aegis of United Nations University and with its help. The biggest states formed on the ruins of the collapsed Soviet Empire are the most backward ones in this respect. For instance on the huge territory of Russia there are only two such centres, in Samara and Nizhny Novgorod. There are certain political, geographical, economic, social and even linguistic factors deterring the implementation of sustainable development methodology in national education systems. Nevertheless it can be fruitfully used on a regional level. This was proved at a number of international research conferences on provincial life and environment held at Samara State University of Architecture and Civil Engineering. A great potential of this philosophy for regional studies even in such restrictive conditions was revealed.